2011
DOI: 10.3727/096368910x536545
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow Stromal Cells and Skin Fibroblasts Inhibit Natural Killer Cell Proliferation and Cytotoxic Activity

Abstract: Mesenchymal stromal cells (MSCs) are potent immunomodulators that have successfully been used to circumvent various types of inflammations, including steroid-resistant graft-versus-host disease. Although initially believed to be restricted to multipotent MSCs, this immunoregulatory function is shared with differentiated cells from the mesenchymal lineage such as skin fibroblasts (SFs). Mesenchymal cell-induced immunoregulation is so potent that it may allow the reactivation of dormant malignancies, a fact that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 45 publications
0
60
0
Order By: Relevance
“…A number of previous reports have shown that MSC can inhibit NK cyotoxicity [23,24,39]. However, these examined resting NK cells, cultured with activating IL-2/15 in the presence of mesenchymal-like cells [23,24,38].…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous reports have shown that MSC can inhibit NK cyotoxicity [23,24,39]. However, these examined resting NK cells, cultured with activating IL-2/15 in the presence of mesenchymal-like cells [23,24,38].…”
Section: Discussionmentioning
confidence: 99%
“…Transplanted MSCs have been shown to inhibit activation of NF-κB, reduce production of TNF-α and IL-6, and increase the expression of anti-inflammatory cytokine IL-10, thereby limiting inflammation after infarction (Du et al, 2008;Onai et al, 2007). Moreover, the increase of indoleaminepyrrole 2,3-dioxygenase (IDO) and PGE2 secretion also reduces T-cell activity and NK cell proliferation (Glennie et al, 2005;Nauta et al, 2006;Pradier et al, 2011;van den Akker et al, 2013). (Yang et al, 2012).…”
Section: Limiting Inflammationmentioning
confidence: 99%
“…The interactions between MSCs and NK cells are bivalent. [2][3][4] In fact, NK cells are capable of killing MSCs only when previously activated. By contrast, MSCs can inhibit interleukin (IL)-2 induced NK cell proliferation and activation.…”
Section: Replymentioning
confidence: 99%
“…By contrast, MSCs can inhibit interleukin (IL)-2 induced NK cell proliferation and activation. [2][3][4] The state of NK cell activation in vivo in our experimental setting has not been explored. However, comparing in vitro the sensitivity to NK cells of the BM-MSCs with that of HLSCs we found that IL-15-activated NK cells killed about 30% of BM-MSCs, whereas NK cells were totally ineffective in killing HLSCs (article in preparation).…”
mentioning
confidence: 99%